1976
DOI: 10.1161/01.cir.54.2.187
|View full text |Cite
|
Sign up to set email alerts
|

The association of increased plasma MB CPK activity and irreversible ischemic myocardial injury in the dog.

Abstract: SUMMARY To evaluate the concordance between elevated plasma MB CPK and irreversible myocardial ischemic injury, coronary occlusion was induced for 10 minutes to 48 hours in 21 open chest dogs and 13 conscious animals. Results of plasma CPK and MB CPK assayed in samples obtained serially for 24 hours were compared to microscopic changes in hearts from the same animals examined 48 hours after occlusion. Twelve of the 34 dogs died within two hours after coronary occlusion. Among the surviving 22 dogs, one failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1978
1978
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(19 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…TTC staining confirmed the absence of infarction in all animals. This finding is consistent with previous studies2' 14,15 showing that the myocardial injury associated with a 15 min coronary occlusion in the dog is completely reversible.…”
Section: Methodssupporting
confidence: 93%
“…TTC staining confirmed the absence of infarction in all animals. This finding is consistent with previous studies2' 14,15 showing that the myocardial injury associated with a 15 min coronary occlusion in the dog is completely reversible.…”
Section: Methodssupporting
confidence: 93%
“…The pathophysiology involved in this process has not yet been completely clarified. Ishikawa et al 13 , however, in experimental studies with dogs, reported that coronary occlusion longer than 20 minutes was associated with enzyme release (total CK and CK-MB) and produced histopathologic evidence of myocardial necrosis (ie, irreversible damage), an observation with relevant diagnostic and therapeutic implications [14][15][16] . In addition, when the combined events were decomposed, we observed that the patients with an elevation in the CK-MB activity after stent implantation had a greater tendency towards mortality (10.6% x 0.6%; P = 0.10) and additional revascularization procedures (30% x 12%; P = 0.14) in one year.…”
Section: Incidence Of Intracardiac Thrombus and Thromboembolism In Thmentioning
confidence: 99%
“…This assumption is based on the observation in cardiac muscle that CK release is an indicator of irreversible damage. 21 The total CKBB per gram of tissue was calculated by taking the measurement of CK in international units in whole brain and the final concentration of purified CKBB obtained in our isolation procedures. …”
Section: Estimation Of Cerebral Infarct Size Based On Serial Changes mentioning
confidence: 99%
“…In several of our animals, there was a secondary rise in CKBB which appeared at various intervals for a variable length of time. If one accepts the premise that a rise in CKBB represents ongoing tissue destruction as occurs in the myocardium, 21 then this secondary rise may represent ongoing destruction from secondary mechanisms, or a further breakdown of the blood brain barrier. It may also explain why with larger infarctions, our method tended to underestimate the actual measured value as shown in figure 6.…”
mentioning
confidence: 99%